Development of competitive PCR for detection of Butyrivibrio fibrisolvens in the rumen - Mrázek, J; Kopecný, J (Folia microbiologica, 2001)
Competitive PCR method was developed for the detection and enumeration of Butyrivibrio fibrisolvens. Sequences of 16S rDNA were obtained from our isolates (serving as a source of data for primer design) and were distinguished into nine different groups of butyrivibria. Specific primers for two distinct groups were designed with the help of BioEdit program. These primers were tested with DNA of 20 strains of ruminal B. fibrisolvens isolates. Annealing temperature 58 degrees C showed a little specificity but a better selectivity was found after raising it up to 65 degrees C. A group 1 competitive fragment of 16S rDNA of different length was constructed using restriction cutting with MspI followed by ligation; the size of the resulting fragment was cut down by 75 bp. The fragment worked in the presence of the original 16S rDNA fragment of B. fibrisolvens JK 609.
Keywords: Gram-Negative Anaerobic Straight, Curved, and Helical Rods; DNA Primers; RNA, Ribosomal, 16S; DNA, Bacterial; Polymerase Chain Reaction; DNA bakterií; Rumen; bachor; RNA ribozomální 16S; polymerázová řetězová reakce; gramnegativní anaerobní tyčinky rovné, zakřivené a spirálovité; DNA, Ribosomal; ribozomální DNA; zvířata; DNA primery; Animals